Manifestations of the bias of an unreliable narrator in novel by V. Domontovich “Doctor Serafikus” - Підодвірна, М. І. (Studia Philologica, 2019)
The results and achievements of the main schools and directions of naratology indicate the need to reread both well-known and recondite texts in order to spell out the meanings. We believe that the narrative analysis of prose by Victor Domontovich (the Ukrainian intellectual writer) is interesting and relevant. The article attempts to characterize the manifestations of the bias of an unreliable narato in the novel “Doctor Seraficus” based on the A. Nyuninga’s cognitive approach. A modern German researcher provides a set of tools that can supplemented for a multidimensional consideration of all ambiguities and contradictions in the text. An intelligent game that unfolds in the text manifests itself at different levels. V. Domontovych conducts the biggest game, the game with meaning through the pending authority of unreliable presenter. The text of the novel consists of abstract reflections, notes, dreams, illusions, fantasies, dreams and retrospective journeys. The main law of the text is the game. Irony and contradictions in the narrator’s words encourage the reader to feel dissonance, uncertainty. Therefore, in a narrative analysis, attention is focused on the speaker and who sees (the focal point). It was investigated that the artist Corvin is the narrator of the novel “Doctor Serafikus”, he tries to give as much as possible objectively the personal story. The motives for the unreliability narration based on the personal interest and bias of the character are determined. We identified the main symptoms of the unreliability of the narrator in the work, and the different levels at which the corresponding narrative is expressed, are highlighted. It is established that an unreliable narrative forces distancing itself from a narrator and takes everything that has been said with caution and detachment. Detailed narrative analysis of the work sheds light on the meanings, which for some reason masked, and allows you to establish artistic functions of an unreliable narrator. We believe that understanding this phenomenon makes it possible to make a comprehensive analysis of artistic text.